Economic analysis of crossbred (Landrace × Desi) pig reared under different floor space allowances - SANDEEP KASWAN; B H M PATEL; S K MONDAL; SANJAY KUMAR; PANCH KISHORE BHARTI; DEEPAK UPADHYAY (Indian Journal of Animal Sciences, 2023)
Present experiment was conducted to study the relative economics of crossbred (Landrace×Desi) pigs with thirty six crossbred barrows reared under 3 different floor space allowances (n=12 each) having group size of 4 pigs/pen. One group (TIS) was provided floor space as per Indian Standards (0.9, 1.35 and 1.8 m2/pig for weaner, grower and finisher stages, respectively) specifications, while other two groups with 33% (T2/3) and 50% (T1/2) reduced floor space allowances. Only covered floor area was provided for all the groups. Different parameters analyzed during the study involved growth, feed conversion efficiency, requirement of water and labour for floor washing, and some other economic variables. Pigs were reared up to 28 weeks of age. Relative economics of pig rearing for three floor space allocation groups was calculated using partial budget analysis. Major performance traits, i.e. average daily gain (ADG) and feed conversion efficiency (FCE) did not differ significantly among the groups. Although body weights of T2/3 and T1/2 groups were marginally higher than TIS group. In contrary to minor savings of labour, large quantity of water was saved in T1/2 and T2/3 groups (805.4 liters/pig and 400.1 liters/pig, respectively) than TIS group between weaner and finisher stages. Additionally, input costs of  ₹` 145 and ` ₹ 96 per pig was saved by providing floor space as per T1/2 and T2/3 groups, respectively than TIS group. It can be concluded that economic gains were maximum in 50% floor space reduction group without adverse effect on performance traits of crossbred pigs.